Legal Protection for the Position of Indonesian Investors in the Joint Venture Agreement - Sri Purwaningsih; Rubiyanto (International Journal of Educational Research & Social Sciences, 2022)
The agreement that forms the basis for developing a joint venture company is the joint venture agreement and articles of association. A joint venture agreement is an agreement between prospective shareholders of a joint venture company subject to the law of contract. The imbalance of position in making Joint Venture Agreements is because foreign participants (Foreign Participants) are more substantial, mainly if foreign parties (Foreign Participants) have cultivated their business strength in the form of multinational (transnational) companies. This imbalance can cause the emergence of such cooperation to be unnatural and result in the strong party controlling the weak party. Such a cooperative relationship becomes a subordinate relationship, not a level relationship, and needs each other. This research aims to find out the concept or theory of legal protection for the Indonesian side in the Joint Venture Agreement. This research is prescriptive normative juridical research. Normative legal research in this study uses secondary data in the form of legal materials obtained through literature studies and emphasizes speculative-theoretical steps and normative-qualitative analysis. It is necessary to improve regulations regarding Joint Venture Agreements to provide legal protection for Indonesia in the Joint Venture Agreement. Because the agreement that forms the basis for developing a joint venture company is a joint venture agreement and articles of association. A joint venture agreement is an agreement between prospective shareholders of a joint venture company subject to the law of contract. The terms of the joint venture agreement should reflect a clear relationship between the parties and describe the development of the relationship in the future.